Characterization of Phenolic Components in Polar Extracts of Eucalyptus globulus Labill. Bark by High-Performance Liquid Chromatography-Mass Spectrometry - Santos, Sónia A. O.
High-performance liquid chromatography electrospray ionization mass spectrometry (HPLC-ESI-MS) and tandem mass spectrometry (MS") were used to investigate the phenolic constituents in methanol, water, and methanol/water extracts of Eucalyptus globulus Labill. bark. Twenty-nine phenolic compounds were identified, 16 of them referenced for the first time as constituents of E. globulus bark, namely, quinic, dihydroxyphenylacetic, and caffeic acids, bis(hexahydroxydiphenoyl (HHDP))-glucose, galloyl-bis(HHDP)-glucose, galloyl-HHDP-glucose, isorhamentin-hexoside, quercetin-hexoside, methylellagic acid (EA) pentose conjugate, myricetin-rhamnoside, isorhamnetin-rhamnoside, mearnsetin, phloridzin, mearnsetin-hexoside, luteolin, and a proanthocyanidin B-type dimer. Digalloylglucose was identified as the major compound in the methanol and methanol/water extracts, followed by isorhamnetin-rhamnoside in the methanol extract and by catechin in the methanol/water extract, whereas in the water extract catechin and galloyl- HHDP-glucose were identified as the predominant components. The methanol/water extract was shown be the most efficient to isolate phenolic compounds identified in E. globulus bark.